THE PREVALENCE AND INTENSITY OF EIMERIA SPP INFECTION IN ETAWAH CROSSBREED GOAT IN SUKAWATI SUB-DISTRICT, GIANYAR BALI - I Dewa Ayu Diah Pradnya Pramita; Ida Ayu Pasti Apsari; Ida Bagus Made Oka; Romy Muhammad Dary Mufa (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Etawah Crossbreed Goat are in demand by farmers because of the variety of products they produce, such as milk, meat, and fur. Coccidiosis is a disease that frequently infects goats in Indonesia and is influenced by host, agent and environment. This study aimed to determine the prevalence and intensity of Eimeria spp infection in etawah crossbreed goat kept in Sukawati District, Gianyar Regency. The number of samples used in this study was 100 feces samples of etawah crossbreed goats in Sukawati District, Gianyar Regency. The design used in this study was cross sectional study. There are two methods of examination carried out, namely qualitative and quantitative methods of examining fecal samples. In qualitative examination using the floating method then the results were analyzed with the chi-square test and quantitative examination using the McMaster method. The results of this study showed that there were 79 samples infected with Eimeria spp. with a prevalence of 79%. The average intensity of Eimeria spp. infection in PE goats in Sukawati District is 740.35 ± 557.05 oocysts/gram. After analysis using chi-square test, it can be concluded that risk factors were not associated with the prevalence of Eimeria spp. infection in PE goats in Sukawati District, Gianyar Regency. Considering the high prevalence of Eimeria spp. infection in PE goats in Sukawati District, Gianyar Regency, it is recommended that farmers increase their concern for cage sanitation and the environment around the cage and routine drug administration.